Frequency, Risk Factors, and Outcome of Acute Kidney Injury Following Bone Marrow Transplantation at Dr Shariati Hospital in Tehran (Iranian Journal of Kidney Diseases, 2010)
Introduction. Bone marrow transplantation (BMT) is a major modality for malignant and hematologic disorders. This procedure is associated with a high morbidity and mortality such as acute kidney injury (AKI). Many factors, such as therapeutic agents, irradiation, and graft versus host disease (GVHD) can cause AKI. Bone marrow transplantation conditioning therapy in Iran is based on drugs such as busulfan and cyclophosphamide and without irradiation therapy. The aim of this study was to evaluate the frequency, risk factors, and mortality of AKI among patients who underwent BMT. Materials and Methods. Acute kidney injury was defined as doubling serum creatinine from baseline at any time during the first 180 days posttransplant. The risk of AKI in relation to non-total-body-irradiation-based conditioning regimen, type of graft (allograft and autograft), comorbidities, GVHD, drug toxicity, and veno-occlusive disease were examined in 375 patients with BMT.Results. One hundred and forty-two patients (37.6%) developed AKI at a median of 18 days after transplant. A higher frequency of AKI was observed in patients who received cyclosporine A (40%), patients with allograft BMT (42.1%), and those who developed gastrointestinal GVHD (47.3%) .The remainder AKI cases were associated with amphotericin B, veno-occlusive disease, and hemolytic-uremic syndrome. Conclusions. The frequency of AKI in our patients with BMT remained high. Cyclosporine A and amphotericin B and the presence of GVHD and veno-occlusive disease increased the risk of AKI within the first 180 days after BMT.